2013
DOI: 10.1098/rsif.2012.0671
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic gene circuits for metabolic control: design trade-offs and constraints

Abstract: A grand challenge in synthetic biology is to push the design of biomolecular circuits from purely genetic constructs towards systems that interface different levels of the cellular machinery, including signalling networks and metabolic pathways. In this paper, we focus on a genetic circuit for feedback regulation of unbranched metabolic pathways. The objective of this feedback system is to dampen the effect of flux perturbations caused by changes in cellular demands or by engineered pathways consuming metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 48 publications
1
67
0
1
Order By: Relevance
“…Second, we have illustrated how to predict trade-offs between the induction level of a synthetic circuit, its function, and the growth of the host. We can therefore benchmark different designs aimed at producing chemicals in biotechnology, where circuits must operate robustly in different growth conditions (53,54). Third, disregulated biogenesis of ribosomes has been suggested as a driver for cancer development (55), and our model may help select, for example, therapeutic targets in the translation machinery.…”
Section: Applicationsmentioning
confidence: 99%
“…Second, we have illustrated how to predict trade-offs between the induction level of a synthetic circuit, its function, and the growth of the host. We can therefore benchmark different designs aimed at producing chemicals in biotechnology, where circuits must operate robustly in different growth conditions (53,54). Third, disregulated biogenesis of ribosomes has been suggested as a driver for cancer development (55), and our model may help select, for example, therapeutic targets in the translation machinery.…”
Section: Applicationsmentioning
confidence: 99%
“…This type of regulation has been widely used in the field of dynamic metabolic engineering to promote and/ or 'robustify' biofuel production under changing environments [72 -75]. In [76], Oyarzú n & Stan provided detailed guidance on the selection of promoters and ribosome binding sites that reflects the trade-offs and constraints of transcriptional feedback for metabolic pathways. More broadly, feedback control has been extensively used in metabolic engineering, which is not the focus of this paper and an indepth review can be found elsewhere [77].…”
Section: Negative Feedback Implementationsmentioning
confidence: 99%
“…biofuels | dynamic metabolic control | transcriptional regulation A grand challenge in synthetic biology is to move the design of biomolecular circuits from purely genetic constructs toward systems that integrate different levels of cellular complexity, including regulatory networks and metabolic pathways (1). Despite the fact that a large volume of regulatory architectures and motifs has been discovered (2,3), little has been accomplished in pathway engineering to improve cellular productivity and yield by exploiting dynamic pathway regulation and metabolic control (4).…”
mentioning
confidence: 99%